Extensive Spinal Epidural Abscess: A Systematic Review of Risk Factors, Clinical Presentation, and Management with a Case Illustration - Hugues Dokponou, Yao Christian; Ontsi Obame, Fresnel Lutece; Mohcine, Salami; Saad, Moussa Elmi; Abderrahmane, Housni; Imbunhe, Napoleão; Mandour, Cherkaoui; Gazzaz, Miloud (World neurosurgery, 2024)
Extensive spinal epidural abscess (ESEA) is a rare clinical entity subject to delayed diagnosis, which can be explained by the extension of the epidural collection, thereby delaying the mass effect responsible for its clinical manifestations. We report a rare case of an extensive C7–T10 epidural abscess in a 54-year-old man treated with antibiotics, laminectomy, and abscess drainage. In addition, we conducted a systematic literature search according to the “Preferred Reporting Items for Systematic Reviews” guidelines. Relevant studies (1980–2023) reporting patients with ESEA were identified from PubMed databases. A total of 48 studies reporting 55 patients were included in this study with a mean age of 55.7 ± 14.6 years with a male predominance of 61.8% (n = 34). The median duration of follow-up was 38 months (21.5–64.3). The mortality rate of ESEA was 1.8% for a 21.8% morbidity rate with 76.4% (n = 42) reported to have been improved after surgery. Both single and multilevel laminectomy with abscess drainage for ESEA leads to patient recovery from this devastating condition. Evaluation of the outcome with data on time-to-Nadir and Nadir-to-surgery is needed to codify ESEA management.